Elasticidades de Armington para o setor automobil??stico no Brasil - Duarte, Filipe Tomaz Figueiredo (2015)
The automobile sector in Brazil is responsible for 20% of the country??s manufacturing sector GDP, and because it is a strategic sector, it is historically supported by the Brazilian government. This paper performs a foreign trade analysis for the automotive sector in Brazil. Elasticities of substitution between imported vehicles and those produced and sold in Brazil, as well as between exported vehicles and those produced for the internal market, are calculated for the period of 1997 to 2015. This approach was first proposed by Armington (1969) and it was use Kume, Tourinho e Pedroso (2007). Using data of total import and export sum of vehicles, domestic, import and export prices, the Armington elasticities are computed according to the methodology of Tourinho, Kume e Pedroso (2007).